VITRINITE REFLECTANCE VARIATION OF OMBILIN COAL ACCORDING TO ITS PETROGRAPHIC ANALYSIS - Binarko Santoso; Bukin Daulay (Indonesian Mining Journal, 2005)
Rank and type variations of the Ombilin coals were studied by petrographic examination of thirty-six samples. The coals are mainly dominated by vitrinite and rare exinite, inertinite and mineral matter.  Vitrinite macerals are dominated by detro- and telovitrinite. Cutinite, liptodetrinite and suberinite are the dominant exinite macerals in the coals. Inertinite macerals in the coals include sclerotinite, inertodetrinite and semifusinite. Mineral matter is rare in the coals consisting of clay and pyrite. The type differences largely reflect climatic influence and differences in peat conditions. The higher vitrinite reflectance of some of the coals is a result of igneous intrusion. The thermally affected coal has vitrinite reflectances between 3.39% and 4.69% indi- cating a coalification stage of anthracite; whereas the thermally unaffected coal is between 0.55% and 0.77% with ranks of sub-bituminous to high volatile bituminous, as classified by the Australian classifica- tion. The thermal effect has also an impact to the vitrinite content in the coals. The thermally affected coals contain 86-99% vitrinite, whereas the thermally unaffected coals contain 80-96% vitrinite. This is because in the thermally affected coals, exinite cannot be distinguished from vitrinite, and it appears to contain high proportion of vitrinite.